Implementation of Working Discipline In Improving Employee Performance: Case Study on the CV. XYZ - Apriyani, Apriyani; Isyanto, Puji; Yani, Dini (Journal Integration of Social Studies and Business Development, 2023)
CV. XYZ is a company engaged in trading goods and services. Employee performance in the organization refers to the ability of employees to carry out the overall tasks that are their responsibility. The importance of employee quality in improving company performance, especially in trade and services, encourages management to always provide coaching and development of existing human resources through training and work motivation to all employees, which are the main variables in improving the quality of their performance. This study aims to determine the application of work discipline in improving the performance of CV employees. XYZ. The method used in this study is a descriptive analysis method with a qualitative approach. Data collection techniques by interviewing and observation. It can be concluded that the application of employee discipline CV. XYZ is still not good because employees are still late for work, play games during working hours, and always procrastinate. The lack of responsibility of employees occurs due to a lack of awareness of each employee.